Does one national prospective payment system market basket make sense? - Cromwell, Jerry (CENTERS for MEDICARE & MEDICAID SERVICES, 1988)
For the first 4 years of Medicare's prospective payment system (PPS), one national market basket of cost weights and price proxies has been used to update payment rates. Previous evidence for a single rate is reviewed, and more recent data are presented that show definite regional differences in input price inflation, resulting in systematic gains or losses for some regions. However, as long as the Health Care Financing Administration continues to periodically update its hospital wage index, the net impact on hospitals is minor. Nevertheless, large differences in PPS-excluded hospital cost shares indicate the need for two sets of cost weights.